2000
DOI: 10.1007/s004050050211
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of cefdinir in the treatment of maxillary sinusitis

Abstract: Cefdinir is a new, extended-spectrum, orally active, third-generation cephalosporin that is resistant to bacterial beta-lactamase production. To evaluate efficacy and safety of the antibiotic in maxillary sinusitis, its use was compared with amoxicillin/clavulanate (amox/clav), which is a well-accepted beta-lactamase-resistant antibiotic. In this investigator-blinded multicenter phase III clinical study, 569 patients were randomly assigned to one of three treatment regimens: one daily dose of cefdinir 600 mg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[52]. These data underscore the potential clinical benefit of selecting an antibacterial with a targeted spectrum of activity, rather than one that is unnecessarily broad spectrum [47,52].…”
Section: Tolerability and Safetymentioning
confidence: 81%
See 2 more Smart Citations
“…[52]. These data underscore the potential clinical benefit of selecting an antibacterial with a targeted spectrum of activity, rather than one that is unnecessarily broad spectrum [47,52].…”
Section: Tolerability and Safetymentioning
confidence: 81%
“…Three randomised clinical trials have shown cefdinir to have efficacy similar to that of other recommended regimens in the treatment of ABRS [3,4,47].…”
Section: Efficacy In Acute Bacterial Rhinosinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…Extended‐spectrum cephalosporins have been shown to be effective, both in vitro and in clinical studies, against the organisms most commonly isolated in ABRS ( Streptococcus pneumoniae , Haemophilus influenzae and Moraxella catarrhalis ) (7,8). One example, cefdinir, has been shown in randomised trials to have clinical cure rates at the test‐of‐cure visit similar to those of amoxicillin/clavulanic acid and levofloxacin in patients with ABRS (8–10) (Table 1). In the study by Henry et al.…”
Section: Recommended Treatment Options For Adults With Abrsmentioning
confidence: 99%
“…Treatment discontinuations caused by gastrointestinal disturbances (e.g. diarrhoea) with cefdinir also appear low and are either comparable or lower than with other antimicrobial agents such as cephalexin (6,7) or amoxicillin/clavulanate (9,10).…”
Section: Why Use Cefdinir In the Treatment Of Usssis?mentioning
confidence: 99%